Anak Penderita Stunting dan Psikologis Orang Tua: Kajian di Desa Teluk, Batanghari - Saripah Saripah (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2022)
The study is background to a reality that needs attention in the gulf village, which is about some of the psychological shymptoms experienced by parents who has stunted children in the Teluk village pemayung district the number of 4 children in the land of kadus 1 for one child, in kadus 3 for one an in kadus 4 for four children, this encouraged the writer to examine some of the factors behind the psychological stress experienced by stunting parents, how high religiustas parents with stunted children, as well as the psychological effects of parents having stunted children in the gulf village. The research is a field/case study using qualitative methonds of data collected through interviews, observation, and documentation, andthen it is analyzed by a descriptive that is to simulate the events in the field. Studies have been found that there is psychological pressure from parents who have stunted children in the bay village of scavenging among otheris this: isolation from surroundings, stress or excessive depression, unbridled emotions, irregular diet and slepp patterns, excessive anxiety and blank talk content contributing factors are the psychological pressure ofcaring parents stunting child in the gulf village district in the neighborhood home, family support, and a lack of community education on stunting as well as at the religious level of parents who have stunting children in the gulf village sub district is: a dimension of worship or practice (ritualistic), the belief dimension (ideology) contains expectations, the refined dimension called the ihsan (application), and the dimension of knowledge.